Characterization of fertility-associated antigens in seminal fluid and their relationship with vital sperm function tests vis-à-vis fertility of breeding buffalo bulls - SINGH, A K; BRAR, P S; CHEEMA, RANJNA S (The Indian Journal of Animal Sciences, 2017)
The present study was undertaken to separate the FAA of seminal plasma and frozen-thawed sperm extracts from 30 buffalo bulls by immunoblotting and determine their relationship with post-thaw sperm function tests visà-vis bull fertility. Eight immunoreactive bands in seminal plasma (60, 55, 45, 33, 31, 18, 16 and 14 kDa) and four in frozen-thawed sperm extracts (65, 55, 48 and 18 kDa) were detected in Western blots. The frozen-thawed semenwas evaluated for first service conception rate (FSCR), per cent acrosome reaction, HOST, viability, DNA integrityand total motility and linked to FAA. In seminal plasma, the bulls positive for 60, 31 and 14 kDa FAA had significantlyhigher FSCR (37.0±3.2 vs 0.0±0.0%, 46.7±3.2 vs 22.5±3.3% and 48.6±3.8 vs 26.0±3.0%), respectively, as compared to their negative counterparts. The FSCR was also higher in detectable FAA-33 than in undetectable FAA-33. Almost all seminal parameters were found to be significantly higher in bulls positive for FAA of 60, 33, 31 and 14 kDa than in their negative contemporary mates. In frozen-thawed sperm extracts, the bulls positive for FAA-65, 48 and 18 had significantly higher FSCR, per cent acrosome reaction and total motility in comparison to their negative herd mates. In conclusion, we have identified buffalo bull seminal FAA that bind to spermatozoa; influence semen quality and subsequent fertility of buffalo bulls.